Discovering Student Engagement across Digital Learning Contexts: A Systematic Review - Andi Nadia Qarirah Rafifah Alisyahbana; M Ahkam Alwi; Haerani Nur (Indonesian Technology and Education Journal, 2026)
Digital learning has rapidly transformed educational practice and raised important questions about how students engage across technology-mediated learning environments; therefore, this systematic literature review aims to examine how student engagement appears in digital learning contexts, identify psychological factors that support or hinder engagement, and analyze how engagement is measured in recent studies. Following PRISMA 2020 guidelines, this review synthesized 24 peer-reviewed studies published between 2021 and 2025 from Scopus, PubMed, and Google Scholar using thematic synthesis. The findings show that student engagement in digital learning consists of behavioral, cognitive, emotional, and agentic dimensions that operate as an interconnected system rather than isolated components. Social connection, instructor responsiveness, self-efficacy, structured interaction, and psychologically safe learning environments were found to support engagement, whereas social isolation, low psychological safety, weak instructional design, excessive flexibility without structure, and digital distraction reduced student involvement. The review also found that engagement measurement remains dominated by self-report questionnaires and platform-based analytics, although these methods capture only partial aspects of engagement and often fail to represent its cognitive and emotional depth. The originality of this review lies in its cross-context synthesis of secondary school and university-level digital learning studies by integrating instructional, psychological, social, and methodological perspectives. The findings imply that meaningful digital engagement should be intentionally designed through responsive teaching, structured interaction, and psychologically supportive learning environments, while future research should adopt mixed-method and longitudinal approaches to capture engagement more comprehensively.